Separation of Variables and the Geometry of Jacobians - Hurtubise, J. (Symmetry, Integrability and Geometry: Methods and Applications, 2007)
This survey examines separation of variables for algebraically integrable Hamiltonian systems whose tori are Jacobians of Riemann surfaces. For these cases there is a natural class of systems which admit separations in a nice geometric sense. This class includes many of the well-known cases.